Pengawasan Kedisiplinan Peserta Didik di SMA Sriguna Palembang - Astuti, Mardiah; Imriani, Putri Zahwa; Ibrahim, Ibrahim (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to understand the process of monitoring student discipline at Sriguna High School in Palembang. This research is qualitative with a descriptive approach. The data collection methods used are interviews, observations, and documentation. The data analysis techniques include data reduction, data presentation, and verification and decision-making. To ensure the validity of the data, triangulation is used, which involves time, method, and source. The results of the study indicate that the process of monitoring student discipline at Sriguna High School in Palembang has been carried out well. This includes monitoring to ensure that students arrive on time, do not skip school, monitor student activities within the school environment, and behave according to established regulations. The supporting factors include supporting school activity plans and good cooperation among educators. The inhibiting factors are the lack of cooperation between parents and students and limited teacher supervision of students. In this study, the author concludes that supervision, monitoring, inspection, guidance and direction, disciplinary actions, and corrective actions are necessary for the student discipline monitoring process to be effective and efficient